2016
DOI: 10.1016/j.tcmj.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Combined expansive open-door laminoplasty with short-segment lateral mass instrumented fusion for multilevel cervical spondylotic myelopathy with short segment instability

Abstract: Objectives:Expansive open-door laminoplasty (EOLP) is an effective procedure for multilevel cervical spondylotic myelopathy (MCSM). It preserves a higher range of cervical motion than laminectomy with fusion and reserves more posterior elements than laminectomy alone. MCSM with short-segment instability or correctable local kyphosis often requires long-segment decompression and adequate segment fusion.Materials and Methods:We retrospectively reviewed 20 patients who received EOLP with short-segment posterior l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…For extensive decompression at the cervico-thoracic region, anterior surgery is least preferred and the appropriate surgical option is either C3-T3 laminoplasty or C3-T3 laminectomy with instrumented postero-lateral fusion. However, multi-level laminoplasty is contraindicated in patients with kyphotic cervical spine as it may lead to further cord compression due to loss of alignment [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For extensive decompression at the cervico-thoracic region, anterior surgery is least preferred and the appropriate surgical option is either C3-T3 laminoplasty or C3-T3 laminectomy with instrumented postero-lateral fusion. However, multi-level laminoplasty is contraindicated in patients with kyphotic cervical spine as it may lead to further cord compression due to loss of alignment [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have successfully treated degenerative multi‐level cervical stenosis and instability with combined open‐door laminoplasty and unilateral screw fixation on the hinged side 7 . Moreover, open‐door laminoplasty with bilateral lateral mass has been utilized for managing multi‐level cervical spondylotic myelopathy and short‐segment instability or correctable local kyphosis 21 . Su et al 31 found that both techniques provide similar outcomes, including maintenance of cervical curvature and improvement of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Pavlov ratio is defined as the sagittal diameter of the spinal canal to that of the vertebral body, and the Pavlov ratios of patients at the C5 level were calculated as previously described. 19 , 20 , 21 , 22 All measurements were repeated three times by two assessors, and the mean value was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect decompression of the spinal cord, a posterior bony ceiling to protect the neural elements, and motion of the spinal segments can be preserved by expanding the spinal canal posteriorly. However, the posterior procedure is contraindicated in patients with segmental instability, major kyphotic alignment, or major anterior pathology [34]. When a patient presents with long-level stenosis combined with short-level segmental instability, local kyphosis, or major anterior pathology, long-level anterior decompression and fusion with or without posterior instrumented fusion may be indicated.…”
Section: Introductionmentioning
confidence: 99%